Salivary IgA subtypes as novel disease biomarkers in systemic lupus erythematosus - Romero-Ramírez, Sandra; Sosa-Hernández, Víctor A.; Cervantes-Díaz, Rodrigo; Carrillo-Vázquez, Daniel A.; Meza-Sánchez, David E.; Núñez-Álvarez, Carlos; Torres-Ruiz, Jiram; Gómez-Martín, Diana; Maravillas-Montero, José L. (Frontiers in Immunology, 2023)
Introduction Immunoglobulin A (IgA) is the main antibody isotype in body fluids such as tears, intestinal mucous, colostrum, and saliva. There are two subtypes of IgA in humans: IgA1, mainly present in blood and mucosal sites, and IgA2, preferentially expressed in mucosal sites like the colon. In clinical practice, immunoglobulins are typically measured in venous or capillary blood; however, alternative samples, including saliva, are now being considered, given their non-invasive and easy collection nature. Several autoimmune diseases have been related to diverse abnormalities in oral mucosal immunity, such as rheumatoid arthritis, Sjogren’s syndrome, and systemic lupus erythematosus (SLE). Methods We decided to evaluate the levels of both IgA subtypes in the saliva of SLE patients. A light chain capture-based ELISA measured specific IgA1 and IgA2 levels in a cohort of SLE patients compared with age and gender-matched healthy volunteers. Results Surprisingly, our results indicated that in the saliva of SLE patients, total IgA and IgA1 subtype were significantly elevated; we also found that salivary IgA levels, particularly IgA2, positively correlate with anti-dsDNA IgG antibody titers. Strikingly, we also detected the presence of salivary anti-nucleosome IgA antibodies in SLE patients, a feature not previously reported elsewhere. Conclusions According to our results and upon necessary validation, IgA characterization in saliva could represent a potentially helpful tool in the clinical care of SLE patients with the advantage of being a more straightforward, faster, and safer method than manipulating blood samples.